Landasan Filosofi Pendidikan Islam dalam Membangun Generasi Berakhlak - Zahrotul Mukarromah; Shobrun Jamil; Naila Afifatun Isfahana; Indah Fatma Maulidiyah (Educational Journal, 2026)
This study examines the philosophical foundations of Islamic education through a literature review method, as an effort to shape a generation with noble morals and a strong personality. The results show that monotheism (tawhid) is the primary foundation of Islamic education because it connects the inner aspects, thought patterns, and behavior of a person in daily life. Islamic education focuses not only on mastering knowledge but also emphasizes the importance of balancing physical and spiritual needs for holistic human development. Furthermore, the primary goal of Islamic education is to shape individuals with good morals, or insan kamil (a perfect human being), who are not only intellectually intelligent but also possess a trustworthy attitude, responsibility, adherence to religious teachings, and a sense of humanity and concern for others. Therefore, Islamic education plays a crucial role in developing a person's character, enabling them to live a life with balanced moral and spiritual values.